Labile Heme Aggravates Renal Inflammation and Complement Activation After Ischemia Reperfusion Injury - Wang, Li; Vijayan, Vijith; Jang, Mi-Sun; Thorenz, Anja; Greite, Robert; Rong, Song; Chen, Rongjun; Shushakova, Nelli; Tudorache, Igor; Derlin, Katja; Pradhan, Pooja; Madyaningrana, Kukuh; et al. (Frontiers in Immunology, 2019)
Background: Ischemia reperfusion injury (IRI) plays a major role in solid organ transplantion. The length of warm ischemia time is critical for the extent of tissue damage in renal IRI. In this experimental study we hypothesized that local release of labile heme in renal tissue is triggered by the duration of warm ischemia (15 versus 45 min IRI) and mediates complement activation, cytokine release and inflammation. Methods: To induce IRI, renal pedicle clamping was performed in male C57BL/6 mice for short (15 min) or prolonged (45 min) time periods. Two and 24 h after experimental ischemia tissue injury labile heme levels in kidney were determined with an apo-horseradish peroxidase assay. Moreover, renal injury, cytokines, and C5a receptor (C5aR) expression were determined by histology, immunohistochemistry and qPCR, respectively. In addition, in vitro studies stimulating bone marrow-derived macrophages with LPS and the combination of LPS and heme were performed and cytokine release was measured. Results: Inflammation and local tissue injury correlated with the duration of warm ischemia time. Labile heme concentrations in renal tissue were significantly higher after prolonged (45 min) as compared to short (15 min) IRI. Notably, expression of the inducible heme-degrading enzyme heme oxygenase-1 (HO-1) was up-regulated in kidneys after prolonged, but not after short IRI. C5aR, the pro-inflammatory cytokines IL-6 and TNF as well as pERK phospohorylation were up-regulated after prolonged, but not short ischemia times. Consecutively, neutrophil infiltration and up-regulation of pro-fibrotic cytokines such as CTGF and PAI were pronounced in prolonged, but not after short ischemia times. In vitro stimulation of macrophages with LPS revealed that TNF and IL-6 release were enhanced in the presence of heme. Finally, administeration of the heme scavenger human serum albumin (HSA) reduced levels of circulating labile heme and the subsequent expression of pro-inflammatory cytokines in kidneys after IRI. Conclusions: Our data show that prolonged warm ischemia times cause increased labile heme levels in the kidney, which correlate with IRI-dependent inflammation and up-regulation of C5aR expression.